2011
DOI: 10.1121/1.3654614
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale direct-test study reveals unexpected characteristics of absolute pitch

Abstract: Absolute pitch, the ability to name a musical note in the absence of a reference note, is very rare in North America and Europe, so that attempts to characterize its features in the western world have involved small numbers of subjects, informal self-report, questionnaires, or web-based exploration. The study reported here capitalized on the high prevalence of absolute pitch in China to explore its features in detail using direct, on-site testing of 160 subjects in a Chinese music conservatory. As expected, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…Thus, speaking a tonal language may help form an association between pitches and their labels, but does not seem to improve one's ability to discriminate between them. These findings are supported by other similar studies on tonal language populations [19,20].…”
Section: Languagesupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, speaking a tonal language may help form an association between pitches and their labels, but does not seem to improve one's ability to discriminate between them. These findings are supported by other similar studies on tonal language populations [19,20].…”
Section: Languagesupporting
confidence: 91%
“…Indeed, research suggests that one must begin learning a language prior to 10-12 years old in order to reach native-level proficiency [29]. This is hardly surprising given the similarity between learning a tonal language and learning AP, as supported by several studies mentioned above [17][18][19][20]. Out of all the reviewed domains, there was the least amount of research on genetic factors involved in AP development.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, AP performance appears to be more accurate for more familiar instruments (Bahr, Christensen, & Bahr, 2005;Ward & Burns, 1982), more accurate for more frequently experienced notes (Deutsch, Le, Shen, & Li, 2011), including white key notes compared to black key notes, (Takeuchi & Hulse, 1991), and even more accurate for individual notes that are used as tuning standards, such as a B-flat for a brass player (Bahr et al, 2005). Moreover, Hedger, Heald, and Nusbaum (2013) demonstrated that the tuning of AP categories in adults is malleable and dependent on environmental input, suggesting that AP categories are not crystallized and immutable after a critical period of learning, but rather can be shifted to accommodate different listening experiences.…”
Section: Introductionmentioning
confidence: 94%
“…Los tonos puros representan una dificultad añadida (Miyazaki, 1989;Rakowski & Morawska-Büngeler, 1987), ya que su potencia sonora disminuye notablemente a medida que nos alejamos de la octava 4, y varía de modo significativo entre las diferentes octavas (Bermudez & Zatorre, 2009). Incluso, más allá del factor registro, se ha probado que el estudio de un determinado instrumento puede comportar una mayor facilidad para identificar ciertos tonos (Baggaley, 1974;Deutsch et al, 2011;Laucirica, 2001;Lockhead & Byrd, 1981;Rakowski & Morawska-Büngeler, 1987;Sergeant, 1969).…”
Section: Sistemas De Evaluación Del Oído Absolutounclassified